Syndecan-1 as a biomarker for sepsis survival after major abdominal surgery. (February 2018) - Holzmann, Maximilian S; Winkler, Martin S; Strunden, Mike S; Izbicki, Jakob R; Schoen, Gerhard; Greiwe, Gillis; Pinnschmidt, Hans O; Poppe, Annika; Saugel, Bernd; Daum, Guenter; Goetz, Alwin E; Heckel, Kai
Aim: Sepsis is a serious complication following surgery and identification of patients at risk is of high importance. Syndecan-1 (sSDC1) levels are known to be elevated during sepsis.Materials & methods: Fifty-five patients scheduled for major abdominal surgery were prospectively included and sSDC1 concentrations were measured during hospital stay.Results: Patients with postoperative sepsis showed a continued increase of sSDC1 levels and exhibited higher median sSDC1 concentrations at day 1 compared with nonseptic patients 90.3 versus 16.5 ng/ml. A significant association of sSDC1 levels with the incidence of sepsis and death was demonstrated.Conclusion: This study identifies sSDC1 as potential biomarker for sepsis and survival after abdominal surgery.